Phytosterol Contents of Edible Oils and Their Contributions to Estimated Phytosterol Intake in the Chinese Diet - Yang, Ruinan (Foods, 2019)
Phytosterols are important micronutrients in human diets. Evidence has shown that phytosterols play an essential role in the reduction of cholesterol in blood and therefore decrease cardiovascular morbidity. In this study, the content and composition of phytosterols in different kinds of vegetable oils were analyzed, and the total phytosterol intake and contribution of foods to intake were estimated based on consumption data. The results showed that the phytosterol contents of rice bran oil, corn oil, and rapeseed oil were higher than those of other vegetable oils and the intake of phytosterol in the Chinese diet was about 392.3 mg/day. The main sources of phytosterols were edible vegetable oils (46.3%), followed by cereals (38.9%), vegetables (9.2%), nuts (2.0%), fruits (1.5%), beans and bean products (1.4%), and tubers (0.8%). Among all vegetable oils, rapeseed oil was the main individual contributor to phytosterol intake (22.9%), especially for the southern residents of China.